Effect of Reinforcement Content and Technological Parameters on the Properties of Cu-4 wt.% Ni-TiC Composites - Jha P.; Gautam R.K.; Tyagi R. (My University, 2025)
The present study deals with the synthesis and investigation of microstructure, density, and hardness behavior of Cu-4 wt.% Ni-TiC metal matrix composites, produced by high-energy ball milling, followed by compaction and sintering. Matrix of Cu-4 wt.% Ni was used, and different weight percentages (0, 2, 4, 6, and 8) of TiC particles were added. The uniform distribution of TiC particles in the matrix alloy was confirmed by characterizing these composite powders by using scanning electron microscope, energy-dispersive spectroscopy, and x-ray diffraction. Both the density and the hardness of the composite containing 4 wt.% TiC were found to be the highest. The density was found to decrease with increasing TiC content beyond 4 wt.%, and it has been attributed to the agglomeration of TiC particles leading to the formation of pores when added in relatively larger amounts. The compressibility behaviors of the milled powders were studied by using Panelli and Ambrosio Filho equation. © 2017, ASM International.